Exploring the Moderating Effects of Organizational Citizenship Behavior on the Relationship between Servant Leadership and Employee Performance with Employee Engagement as the Mediator - Fakhri, Mahendra (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The objective of this research is to explore the moderating effect of organizational citizenship behavior on employee performance. Servant leadership is a leadership style that prioritizes serving others and promoting their well-being. It has been found to have positive outcomes such as employee engagement, organizational citizenship behavior, and employee performance.Methodology: The method used in this research is the quantitative research, with a population consisting of female employees. The sample comprised 310 female employees who were led by female leaders, and selected using simple random sampling. To explore the relationships among variables and incorporate mediating and moderating effects in the model, SEM-PLS was employed.Finding: Interestingly, when considering OCB as a moderating variable, different results were observed for direct and indirect effects. The indirect effect revealed that OCB had a positive and significant moderating effect on the relationship between servant leadership and employee performance, suggesting that OCB enhanced this relationship. Conclusion: However, when examining the direct effect of servant leadership on employee performance while moderated by OCB, a significant but negative association between these variables suggests weakened relationships. This finding suggested that OCB played a significant role in moderating the relationship between Servant Leadership and Employee Performance, emphasizing the need to recognize OCB as an essential factor in comprehending the impact of servant leadership on employee performance.